Michelin Rated Cuisine Through the Lens of Food Films: Analysing the Hundred-Foot Journey and Ratatouille - Wan, Jean (The School of Hospitality & Tourism at Auckland University of Technology, 2025)
This article explores the representation of Michelin-level cuisine in film as a lens to examine cultural identity, hierarchy, and transformation in the culinary world. Through an analysis of The Hundred-Foot Journey (Halström, 2014) and Ratatouille (Bird & Pinkava, 2007), the study highlights the dual nature of the Michelin system as both aspirational and exclusionary. While The Hundred-Foot Journey critiques Eurocentric culinary traditions through the experiences of a migrant chef, Ratatouille employs anthropomorphism to challenge traditional notions of legitimacy in fine dining. By examining these films, this article contributes to the discourse on food films and their role in shaping contemporary understandings of gastronomy and cultural identity.
Keywords: 36 Creative Arts and Writing; 47 Language, Communication and Culture; 4702 Cultural Studies; 3605 Screen and Digital Media